(3GdWQjb Gdi eLJeY GdeYQaI h ehGLgI GdaLhI GdJcfhdhLjI aj eUQs - (3UdGM(B, (3Rjf GdOjfs ((3GdbGgQI(B:s (3ecJHI GdTQhb GdOhdjI(B,s, 2002)
(3GdGfJbGd ef YUQ GdUfGYI Gdi YUQ GdeYdheGJ h eGgjI JcfhdhLjG GdeYdheGJ h ehGLgI GdJNda h WHjYI GdJMhd Gdi GbJUGO GdeYQaI ceG Je JfGhd Gge GSJNOGeGJ h JWHjbGJ JcfhdhLjG GdeYdheGJ h JCKjQGJgG Ydi eSJhi GdJTZjd h eYOdGJ Gdfeh h TQhW fLGM JcfhdhLjG GdeYdheGJ ddbjGe HOhQgG GdJfehj ceG Je GdJWQb Gdi OhQ GdJcfhdhLjG aj JbSje GdYed GdOhdj h GdOhd GdfGejI h ehGLgI GdaLhI GdJcfhdhLjI h OhQ GdGJaGbjGJ h GdefXeGJ GdOhdjIaj GfJTGQ JcfhdhLjG GdeYdheGJ h CNjQG hGbY UfGYI JcfhLjG GdeYdheGJ h GdGJUGdGJ aj eUQ h GdGWGQ GdJTQjYj h GdeDSSj GdeDKQ aj JcfhdhLjG GdeYdheGJ h OQGSI deTcdGJ GdWdH h GdYQV dJcfhdhLjG GdeYdheGJ aj eUQ h UfGYI HQeLjGJ GdceHjhJQ aj eUQ h CecGfjGJ JWhjQgG (B..s
(3eQGLY U(B.141s
Keywords: (3GdJfejIs; (3JcfhdhLjG GdeYdheGJs